1999
DOI: 10.1038/sj.onc.1203164
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D3 accumulation and activity integrate and rank the comitogenic pathways of thyrotropin and insulin in thyrocytes in primary culture

Abstract: The proliferation of most normal cells depends on the synergistic interaction of several growth factors and hormones, but the cell cycle basis for this combined requirement remains largely uncharacterized. We have addressed the question of the requirement for insulin/ IGF-1 also observed in many cell culture systems in the physiologically relevant system of primary cultures of dog thyroid epithelial cells stimulated by TSH, which exerts its mitogenic activity only via cAMP. The induction of cyclin A and cdc2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 59 publications
4
48
0
Order By: Relevance
“…The different mitogenic stimulations (TSH, cAMP, growth factors) require the activity of CDK4 , and converge on the inactivating phosphorylation of pRb and related proteins p107 and p130 (Coulonval et al, 1997;Van Keymeulen et al, 1999), on the phosphorylation and nuclear translocation of CDK2, and on the induction of cyclin A and CDK1 (Baptist et al, 1996). These effects are dependent on insulin (Coulonval et al, 1997;Van Keymeulen et al, 1999).…”
Section: Our Present Knowledge Of Signal Transduction Pathways Comentioning
confidence: 99%
See 2 more Smart Citations
“…The different mitogenic stimulations (TSH, cAMP, growth factors) require the activity of CDK4 , and converge on the inactivating phosphorylation of pRb and related proteins p107 and p130 (Coulonval et al, 1997;Van Keymeulen et al, 1999), on the phosphorylation and nuclear translocation of CDK2, and on the induction of cyclin A and CDK1 (Baptist et al, 1996). These effects are dependent on insulin (Coulonval et al, 1997;Van Keymeulen et al, 1999).…”
Section: Our Present Knowledge Of Signal Transduction Pathways Comentioning
confidence: 99%
“…In dog thyrocytes, the formation and the nuclear translocation of essential cyclin D3-CDK4 complexes depend on the synergistic interaction of TSH and insulin. The presence of the required cyclin D3 depends on insulin/IGF-I (Van Keymeulen et al, 1999), whereas TSH stimulates the assembly of the cyclin D3-CDK4 complexes and their import into nuclei (Depoortere et al, 1998;Van Keymeulen et al, 1999) where these complexes are anchored by their association with p27 kip1 (Depoortere et al, 2000;. This also sequesters p27 away of CDK2 complexes (Depoortere et al, 2000), thus contributing to CDK2 activation.…”
Section: Our Present Knowledge Of Signal Transduction Pathways Comentioning
confidence: 99%
See 1 more Smart Citation
“…23 The expression of cyclin D3 supported by facilitative comitogenic factors (insulin and carbachol) is specifically required in the cAMP-dependent cell cycle, but not in the mitogenic stimulation by growth factors that induce cyclin D1. 23,49 cAMP promotes the assembly of cyclin D3-CDK4 complexes, 23,49 their nuclear import associated with their binding to p27, 50,28 and then stimulates the Thr172 phosphorylation and activity of CDK4 within this complex. 25 In this study, two new essential features of these distinct mitogenic modes are reported, initially deriving from the same experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In dog thyrocytes primary culture, the roles of TSH (cAMP) and insulin/IGF-1 on cell cycle progression have been recently found to be distinct and complementary (6). Their signaling pathways are largely independent.…”
mentioning
confidence: 99%